Correlation between molecular prognostic factors and bevacizumab therapeutic resistance in patients with metastatic colorectal cancer; the AVAMET study - Adrian Paul Suceveanu; Dragos Serban; Andreea Daniela Caloian; Georgeta Camelia Cozaru; Anca Chisoi; Anca Antonela Nicolau; Ioan Sergiu Micu; Andra Iulia Suceveanu (Journal of Mind and Medical Sciences)
Objectives. Colorectal cancer is responsible for more than two million cases diagnosed annually. Despite early diagnosis through screening programs and adequate treatment, 25% of cases are diagnosed with metastatic disease while up to 50% of patients diagnosed early progress to metastatic disease. Materials and Methods. The study of 40 patients aims to identify the role of placental growth factor and heparin-binding growth factor as prognostic tools for current treatments involving resistance to bevacizumab in metastatic colorectal cancer. Results. Our results suggested that overall survival was influenced by serum fibroblast growth factor 1 levels. A cut-off value of 260.71 pg/ml was considered predictive of a disease-free survival/DFS of 6 months to 1 year, while a cut-off value of 117.51 pg/ml was considered predictive of a better DFS. Regarding placental growth factor involvement, a serum level of 13.75 pg/ml as a first determination and 11.48 pg/ml after 8 months of chemotherapy and anti-vascular endothelial growth factor therapy were considered cut-off values for 1- to 3-year overall survival/OS, while 6.45 pg/ml and 8.12 pg/ml levels were considered cut-off levels for 3- to 5-year OS. Conclusions. The results of the current study detected cutoff levels that may better predict treatment resistance in advanced-stage colorectal cancer and poor OS and DFS rates. Serum levels of placental growth factor and fibroblast growth factor 1 at diagnosis become important prognostic factors predicting resistance to bevacizumab in metastatic colorectal cancer.